Youth Cultures, Transitions, and Generations
XV, 195 p.
Keywords: Within contemporary youth research there are two dominant streams - a 'transitions' and a 'cultures' perspective. This collection shows that it is no longer possible to understand the experience of young people through these prisms and proposes new conceptual foundations for youth studies, capable of bridging the gap between these approaches.